2017
DOI: 10.3390/jcm6090088
|View full text |Cite
|
Sign up to set email alerts
|

Can Diet Help Non-Obese Individuals with Non-Alcoholic Fatty Liver Disease (NAFLD)?

Abstract: Subjects diagnosed with non-alcoholic fatty liver disease (NAFLD) or hepatic steatosis are usually obese or overweight. NAFLD has also been reported in many non-obese healthy subjects as an incidental finding during imaging. Subjects with early-stage NAFLD who are otherwise healthy are often left unmanaged in current clinical practice; it is not clear if an early intervention in those individuals would be of any benefit in preventing NAFLD progression to more serious conditions. Since many of these subjects ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…described that like obese NAFLD patients, lean NAFLD patients can get benefits in dietary modification as well as weight reduction strategy. [16] This data is also supported by another study that concluded that change in the body weight is a potent independent issue for both the development and regression of NAFLD in non-obese individuals, regardless of baseline BMI. [17] As none of the study focused on the benefits of weight reduction on histological activity in patients with lean NASH, the study was focused to explore the effect of weight reduction strategy in lean NASH individuals.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…described that like obese NAFLD patients, lean NAFLD patients can get benefits in dietary modification as well as weight reduction strategy. [16] This data is also supported by another study that concluded that change in the body weight is a potent independent issue for both the development and regression of NAFLD in non-obese individuals, regardless of baseline BMI. [17] As none of the study focused on the benefits of weight reduction on histological activity in patients with lean NASH, the study was focused to explore the effect of weight reduction strategy in lean NASH individuals.…”
Section: Introductionsupporting
confidence: 61%
“…Therefore, diet and lifestyle modification, with weight reduction remains the mainstay of treatment in these patients. [16,22] Previous studies testing the effectiveness of lifestyle modification in NAFLD have found that 7 to 10% weight loss is accompanied by a remarkable normalization of liver enzymes and a systematic reduction of liver fat. [29] But, no previous study tested the effect of weight reduction on non-obese lean NASH patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies have found that high fructose intake is linked to fatty liver disease via gut microbiota changes in NAFLD patients of normal weight 37. Given the importance of dietary carbohydrates in the aetiology of NAFLD, we hypothesised that restricting carbohydrate intake without reducing calorie intake might be an appropriate strategy in patients with normal weight 10–12. Although several studies have examined the effects of macronutrient manipulation among patients with NAFLD,38 39 we are aware of no study that evaluated the effects of a moderate carbohydrate-restricted diet, without weight loss, in normal-weight individuals with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The main effective strategy for management of NAFLD is weight loss 9. Given the key role of dietary carbohydrates in the development of NAFLD, it seems that a moderate restriction of carbohydrates, even without inducing any significant weight loss, might improve the fat content of the liver in normal-weight individuals with NAFLD 10–12. Earlier evidence has shown the efficacy of this dietary pattern in controlling inflammation and other metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%